Evaluatıon of contrast enhancement intensity, pattern, and kinetics of breast lesions on contrast-enhanced spectral mammography - Ayşe Füsun Bekirçavuşoğlu; Sibel Kul; Süleyman Bekirçavuşoğlu; Dilara Atasoy; Merve Erkan (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Contrast-enhanced spectral mammography (CESM) is a new and promising imaging modality that improves tumor visibility through tumor contrast enhancement caused by malignant neovascularization. Breast magnetic resonance imaging (MRI) is based on the principle that hypervascular lesions are stained more intensely with contrast material than the breast glandular tissue. Currently, contrast enhancement in contrast-enhanced mammography is used only as a tumor marker, and it is unclear whether it is possible to analyze the amount, pattern, and kinetics of contrast enhancement using this technique and the contribution of such analyses to the diagnostic process. Objective To investigate the contribution of qualitative and semiquantitative data obtained from contrast-enhanced spectral mammography images to benign-malignant differentiation and their relationship with prognostic factors. Methods This retrospective study included 64 patients who were treated between 2015 and 2019. A pathological breast craniocaudal (CC) radiograph was obtained 2 min after contrast. Following the standard procedure, pathological breast CC radiography was performed for approximately 6 min. The amount of contrast enhancement, contrast enhancement patterns, and kinetics of the breast lesions were analyzed qualitatively and/or semiquantitatively using contrast-enhanced mammography images. The contribution of the evaluated radiological parameters to the benign-malignant differentiation of tumors and their relationship with histopathological prognostic markers was also evaluated. Results Nine benign and 55 malignant cases were identified in this study. The results showed that malignant tumors had a higher average contrast-to-noise ratio (CNR) than benign tumors, and a strong correlation was observed between semiquantitative and qualitative contrast amounts(R > 0.564, p ≤ 0.001). Benign tumors exhibited persistent enhancement, whereas malignant tumors showed plateau and washout enhancement patterns. Additionally, estrogen receptor (ER) positivity and tumor grade were linearly related to the degree of late-phase enhancement in malignant tumors. Patients with a high Ki-67 proliferation index were more likely to exhibit type-3 curves. Conclusions Kinetic patterns and enhancement results of CESM can be utilized in the characterization of masses and may serve as a prognostic factor.